Oro-mucosal administration of oxytocin using medicated lollipops alters social attention, similar to intranasal and lingual routes: Implications for therapeutic use - Xu, Dan; Li, Qin; Zhuang, Qian; Zhang, Yingying; Yao, Shuxia; Zhao, Weihua; Kendrick, Keith M. (Frontiers in Neuroscience, 2022)
A key functional effect of intranasal administration of the neuropeptide oxytocin is on top-down control of social attention. However, an oro-mucosal administration route may be better tolerated for chronic therapeutic use and evidence suggests that some functional effects of oxytocin can be mediated via peripheral routes. The current study investigated if oxytocin administered orally using medicated lollipops can both increase blood oxytocin concentrations and influence social attention and state anxiety. In a randomized, double-blind, clinical trial adult male participants received oral oxytocin (24 IU) or placebo 30-min before completing a well-established anti-saccade paradigm which can assess treatment effects on both top-down and bottom-up attention. Oxytocin administration modulated top-down social attentional processing by increasing anti-saccade error rates on both social and non-social stimuli although it only increased response latencies for social cues. Anti-saccade errors were also positively associated with the proportionate increase in plasma oxytocin concentrations. A comparison analysis showed that oral oxytocin administration increased blood concentrations to a similar degree as given by lingual spray, although less than when given intranasally. Importantly, attentional and anxiolytic effects of oxytocin in the anti-saccade task were similar across intranasal, lingual, and oral administration routes. These findings demonstrate that oral administration of oxytocin, similar to via intranasal and lingual routes, can modulate top-down social attention and state anxiety and support its potential for therapeutic use. They also provide further evidence that functional effects of exogenously administered oxytocin can be mediated indirectly either by crossing the blood brain barrier or producing receptor mediated vagal stimulation, as opposed to via direct entry into the brain.